Manufacturing of Ultra-Thin X-ray-Compatible COC Microfluidic Devices for Optimal In Situ Macromolecular Crystallography Experiments - Ramakrishna Vasireddi; Antonin Gardais; Leonard M. G. Chavas (Micromachines, 2022)
Cyclic-olefin-copolymer (COC)-based microfluidic devices are increasingly becoming the center of highly valuable research for in situ X-ray measurements due to their compatibility with X-rays, biological compounds, chemical resistance, optical properties, low cost, and simplified handling. COC microfluidic devices present potential solutions to challenging biological applications such as protein binding, folding, nucleation, growth kinetics, and structural changes. In recent years, the techniques applied to manufacturing and handling these devices have capitalized on enormous progress toward small-scale sample probing. Here, we describe the new and innovative design aspects, fabrication, and experimental implementation of low-cost and micron-sized X-ray-compatible microfluidic sample environments that address diffusion-based crystal formation for crystallographic characterization. The devices appear fully compatible with crystal growth and subsequent X-ray diffraction experiments, resulting in remarkably low background data recording. The results highlighted in this research demonstrate how the engineered microfluidic devices allow the recording of accurate crystallographic data at room temperature and structure determination at high resolution.